Analysis of the relationship between the amount of training and cognitive expertise. A study of young volleyball players - Gil, A.; Moreno, M. P.; Moreno, A.; Garcia-Gonzalez, L.; Claver, F.; Del Villar, F. (The Journal of Strength and Conditioning Research, 2013)
The main goal of this research was to analyze the relationship between the amount of practice accumulated in training and the level of cognitive expertise achieved by volleyball players who are still in training. Another goal was to determine the number of training hours per week needed to improve knowledge significantly. The study's sample was composed of 520 volleyball players between the ages of 12 and 16 years. The independent variable was the amount of training, defined as the number of weekly hours that the volleyball player devoted to training. The dependent variable was cognitive expertise, measured by declarative knowledge and procedural knowledge. A univariate analysis of variance was done to examine the relationship between the number of weekly hours and the declarative and procedural knowledge reached by volleyball players in the athletic formation training stages. Statistical significance was set at p < 0.05. There were significant differences in knowledge according to the number of weekly training hours (p < 0.001). These results confirm that there is a relationship between the quantity of practice and the development of cognitive expertise. It is recommended that young players dedicate at least 4 hours weekly to training to achieve a significant improvement in cognitive expertise.